STRATEGI MEMBANGUN NATION BRANDING INDONESIA DALAM ASIAN GAMES JAKARTA-PALEMBANG 2018 - Romi Iriandi Putra (Universitas Teuku Umar, 2020)
The Asian Games 2018 is a sporting event held every 4 years, bringing together all Asian athletes from various branches to compete for the country's pride. Indonesia was chosen to be the host of the Asian games which made the right momentum to build Indonesia's nation branding. This study analyzes how the strategy of building nation branding on the momentum of Asian games 2018 Jakarta - Palembang. This research uses a descriptive qualitative method by describing related data. The results in this study show that the strategy used to build a nation branding in the Asian Games with media management, accentuate elements of Indonesian culture, conducting global diplomacy, creating mutual collaboration branding, and conducting a post events campaign. In addition to building nation branding, need several elements namely brand identity, positioning, and brand image which all focus on one goal that is to increase trading, tourism, and also an investment in the country.Kata Kunci: Asian games, nation branding, place marketing, brand image, destination branding.